Characterization of Testis-Derived Mesenchymal Cells and the Hunt for Universal Stemness Markers - Ghabriel, Myret (AUC Knowledge Fountain, 2022)
Mesenchymal stromal/stem cells (MSCs) are multipotent cells residing in multiple tissues with the capacity for self-renewal and differentiation into various cell types. Due to the myriad sources of MSCs the International Society for Cellular Therapy (ISCT) proposed certain criteria for their characterization. Here, we isolate adult MSCs from mouse testes and demonstrate that these testis-derived MSCs (tMSCs) follow some of the ISCT’s criteria. tMSCs expressed the MSCs surface markers CD44, CD73, and CD29 and lacked the expression of the hematopoietic cell marker CD45. Moreover, the cells displayed the capacity for self-renewal and in vitro differentiation into adipocytes. Since the isolation of MSCs from mouse testes is considered novel we wanted to study the transcriptomes of other mouse derived MSCs to compare their data to our results. Using transcriptomic analysis, we examined the expression of the MSCs markers in mouse bone marrow-derived and adipose tissue-derived MSCs and compared them to the results aquired in our lab for tMSCs. Mouse derived MSCs and tMSCs were CD29+, CD44+, and CD45. Alas, the criteria for MSCs identification proposed by ISCT is not always consistent across different tissue sources. It has been shown to fall short in describing MSCs populations derived from different species and tissues of origin. Since the proper identification of MSCs is critical in yielding pure populations for successful therapeutic applications, we aimed to address this shortcoming by identifying potential markers to be used collectively with the ISCT’s criteria to provide more accurate means for MSCs identification. In our study, we carried out comparative expression analysis between human and mouse MSCs derived from multiple tissues to identify the common differentially expressed genes. We show that six members of the proteasome degradation system are similarly expressed across bone marrow, adipose tissue, amnion and umbilical cord derived MSCs. Also, with the help of predictive models, we found that these genes successfully identified MSCs across all the tissue sources tested. Moreover, using genetic interaction networks, we show a possible link between these genes and antioxidant enzymes in the MSCs antioxidant defense system, thereby pointing to their potential role in prolonging MSCs’ life span. Our results suggest these genes can be used as stemness-related markers.